Functionalized solid lipid nanoparticles combining docetaxel and erlotinib synergize the anticancer efficacy against triple-negative breast cancer - Chaudhuri A.; Naveen Kumar D.; Kumar D.; Kumar Agrawal A. (My University, 2025)
The goal of the study was to fabricate folic acid functionalized docetaxel (DOC)/erlotinib (ERL)-loaded solid lipid nanoparticles (SLNs) to synergistically increase the anticancer activity against triple-negative breast cancer. DOC/ERL-SLNs were prepared by the high shear homogenization – ultrasound dispersion method (0.1 % w/v for DOC, and 0.3 %w/v for ERL) and optimized using Plackett Burman Design (PBD) followed by Box Behnken Design (BBD). The optimized SLNs demonstrated particle size < 200 nm, PDI < 0.35, and negative zeta potential with entrapment and loading efficiency of ∼80 and ∼4 %, respectively. The SLNs and folic acid functionalized SLNs (FA-SLNs) showed sustained release for both drugs, followed by Higuchi and Korsemeyer-Peppas drug release models, respectively. Further, the in vitro pH-stat lipolysis model demonstrated an approximately 3-fold increase in the bioaccessibility of drugs from SLNs compared to suspension. The TEM images revealed the spherical morphology of the SLNs. DOC/ERL loaded SLNs showed dose- and time-dependent cytotoxicity and exhibited a synergism at a molar ratio of 1:3 in TNBC with a combination index of 0.35 and 0.37, respectively. FA-DOC/ERL-SLNs showed enhanced anticancer activity as evidenced by MMP and ROS assay and further inhibited the colony-forming ability and the migration capacity of TNBC cells. Conclusively, the study has shown that SLNs are encouraging systems to improve the pharmaceutical attributes of poorly bioavailable drugs. © 2024 Elsevier B.V.